'Microwave assisted facile green synthesis of carrageenan carbon dots(CDs) and their interaction with Hisbiscus Rosa sinensis leaf cells'. Issue 12 (26th September 2022) - Suhail, Basharat; Bajpai, S. K.; Souza, A. D'
ABSTRACT: In the present work, Carrageenan has been used as precursor to prepare carbon dots (CD) via microwave-assisted synthesis. The carbon dots, as synthesised, were characterised by various analytical techniques such as Fourier Transformation Infra-Red (FTIR) spectroscopy, X-ray diffraction (XRD), Transmission Electron Microscopic (TEM) analysis, UV-Vis spectroscopy and Fluorescent Microscopy (FM). Their size range was found to be 25 to 30 nm and the zeta potential of particles was found to be −14.98 mv. Finally, impregnation of CDs was studied in Hisbiscus Rosa sinensis leaf. It was observed that as the concentration of CDs solution increased, percent insertion (PI) also increased, but the time required for maximal insertion decreased with increasing concentrations of CDs in the feed solutions. In addition, number of CDs inserted decreased after attainment of maximum number, a fairly high concentration of CDs was observed in stomata, as viewed through fluorescence microscope.